Методико-алгоритмічне забезпечення функціонування мобільного комплексу з оцінки вібраційного стану енергетичних агрегатів - Єфремов, Ю. Г. (НТУ "ХПІ", 2015)
Описано методико-алгоритмічне забезпечення мобільного вимірювально-діагностичного комплексу оцінки технічного стану енергообладнання по параметрах вібрації. Програмне забезпечення комплексу складається з модулів реєстрації, візуалізації й первинної обробки інформації, автоматизованого контролю вібраційного стану, аналізу вібропараметрів і визначення дисбалансу роторів. Наведено приклад експериментальних досліджень вібраційного стану допоміжного обладнання (димосос Д-25Х2ШБ) енергоблоку. Визначено, що в СКЗ віброшвидкості опор димососа значний вклад вносить низькочастотна вібрація (1–10 Гц).

Methodical -&-algorithmic software for the portable metering and diagnostic system intended for the assessment of the operating conditions of the electric equipment in terms of vibration parameters has been described. The system software includes several independent modules, in particular for the registration, monitoring and analysis. The registration module is intended for the collection, visualization and primary information processing. The monitoring module is intended for the computer-aided control of the vibratory state of the equipment. This module allows for the monitoring of the range of the vibratory displacement of the rotors, vibration velocity root-mean-square (RMS) value of the supports, rotation speed and other parameters of mechanical values, and also for the formation of the trends of vibration parameters and the determination of their sudden change (a leap). The analysis module is intended for the determination of spectral and harmonic characteristics of the vibratory displacement of the rotors and the vibration velocity of the supports and also for the determination of the rotor out-of-balance in terms of the vibration parameters of the rotors and supports. Using the mobile system the experimental estimate of the vibratory state of the auxiliary equipment (smoke sucker D-25X2ShB) of the energy block has been carried out. It has been established that the low-frequency vibration (1 to 10Hz) contributes significantly to the RMS value of the vibration velocity of smoke sucker supports.
Methodical and algorithmic software for the functioning of the portable system to assess the vibratory state of power units
Keywords: вимірювально-діагностичний комплекс; вібраційні параметри; система діагностики; спектральні характеристики; vibration; vibratory state; diagnostic system; spectral characteristics